Role of dysregulated cytokine signaling and bacterial triggers in the pathogenesis of Cutaneous T Cell Lymphoma - Fanok, Melania H. (J Invest Dermatol, 2017)
Cutaneous T cell lymphoma is a heterogeneous group of lymphomas characterized by the accumulation of malignant T cells in the skin. The molecular and cellular etiology of this malignancy remains enigmatic and what role antigenic stimulation plays in the initiation and/or progression of the disease remains to be elucidated. Deep sequencing of the tumor genome revealed a highly heterogeneous landscape of genetic perturbations and transcriptome analysis of transformed T cells further highlighted the heterogeneity of this disease. Nonetheless, using data harvested from high-throughput transcriptional profiling allowed us to develop a reliable signature of this malignancy. Focusing on a key cytokine signaling pathway, previously implicated in CTCL pathogenesis, JAK/STAT signaling, we used conditional gene targeting to develop a fully penetrant small animal model of this disease that recapitulates many key features of mycosis fungoides, a common variant of CTCL. Using this mouse model, we demonstrate that T cell receptor engagement is critical for malignant transformation of the T lymphocytes and that progression of the disease is dependent on microbiota.